Constipation is not associated with colonic diverticula: a multicenter study in Japan. Issue 3 (3rd December 2014) - Yamada, E.; Inamori, M.; Watanabe, S.; Sato, T.; Tagri, M.; Uchida, E.; Tanida, E.; Izumi, M.; Takeshita, K.; Fujisawa, N.; Komatsu, K.; Hamanaka, J.; et al.
Abstract Background The association of diverticula with bowel habits is unclear. We therefore analyzed the association between diverticula and bowel habits in over 1000 Japanese individuals. Methods Japanese subjects who underwent total colonoscopies at seven centers in Japan from June to September 2013 were analyzed. Bowel habits were evaluated using the Gastrointestinal Symptom Rating Scale, and stool form was assessed using a part of the Bristol Scale and Rome ΙΙΙ criteria. Diverticula were diagnosed by colonoscopy with a transparent soft‐short hood. Key Results The study evaluated 1066 subjects, 648 males and 418 females (ratio, 1.55 : 1), of mean age 63.9 ± 13.0 years. After adjusting for age and sex, the presence of constipation was associated with a significantly reduced likelihood of diverticula (odds ratio [OR] = 0.70, 95% confidence interval [CI] 0.52–0.93). When assessed according to the location of diverticula, the presence of constipation was associated with a significantly decreased likelihood of left‐sided (OR = 0.39, 95% CI 0.16–0.93), but not right‐sided (OR = 1.10, 95% CI 0.48–2.53), diverticula. Furthermore, stool form was unrelated with the presence or absence of diverticula. Conclusions & Inferences The wide‐spread hypothesis that constipation was associated with colonic diverticula was not supported. Rather, we found that the absence of diverticula was associated with constipation, suggesting the need to reassess the etiology of colonic diverticula.